Pengembangan Modul Bimbingan dan Konseling Berbasis Profetik untuk Tujuh Kebiasaan Anak Indonesia Hebat di SMP - Tri Anjar; Retno Fajarwati; Agus Wibowo (Journal of Society Counseling, 2026)
This research aims to produce a prophetic value-based guidance and counseling module as a guidance and counseling medium to implement the program of the seven habits of great Indonesian children at the junior high school level. Although character-strengthening policies have been widely promoted, no guidance and counseling module has yet been specifically designed to integrate the recently launched Seven Habits of Great Indonesian Children movement with prophetic values at the junior high school level; this gap constitutes the novelty of the present study. The research uses development research with the ADDIE model (Branch, 2009), which includes the stages of analysis, design, development, implementation, and evaluation. The subjects of the study were nine (n = 9) junior high school guidance and counseling teachers in Metro City representing State, religious-based, and public junior high schools, together with three experts in guidance and counseling, design, and language. Data were collected through validation and practicality questionnaires using a four-point Likert scale and analyzed using quantitative descriptive techniques. The results show that the prophetic-based module obtained a very feasible category (mean = 3.62; 90.42%) in the aspects of content, design, and language, and a very practical category (mean = 3.58; 89.40%) for use by guidance and counseling teachers. This study concludes that prophetic-based guidance and counseling modules are suitable for use as practical guides in the implementation of character education through the Seven Habits of Great Indonesian Children.